The Hemingway tradition - Butcher, Kristin (Custer, Wash : Orca Book Publishers, 2002)
After his father commits suicide, Shaw struggles to come to terms with the death and move on.
Keywords: Parents -- Death -- Fiction; Suicide -- Fiction